Implementing Little Fox Chinese Video-Tailored Instruction in A Mandarin Listening Class - Karina Fefi Laksana Sakti (Research And Innovation In Language Learning (RILL), 2021)
Listening skills are the first skills that must be mastered by learners before moving on to speaking, reading and writing skills. In the conditions of the Covid-19 pandemic, teaching and learning activities are carried out online, therefore educators must have more effective learning strategies such as the use of learning media. This study discusses the application of video listening to Little Fox Chinese in Mandarin. This research is a qualitative descriptive research type because this study aims to describe the application of the Little Fox Chinese video in Listening 1 subject in the Mandarin Education Study Program, Universitas Negeri Malang. The application of the Little Fox Chinese video was carried out in three stages, namely the initial, main, and final learning activities. Based on the results of observations, it can be concluded that the teaching and learning activities of listening 1 subjects with the application of the Little Fox Chinese video go smoothly and conducive. Based on the results of the interview, students revealed that the Little Fox Chinese video media was very interesting.